200 Years of Research on Himalayan Biodiversity: Trends, Gaps, and Policy Implications - Rana, Suresh K.; Rawal, Ranbeer S.; Dangwal, Bhawana; Bhatt, Indra D.; Price, Trevor D. (Frontiers in Ecology and Evolution, 2021)
Global mountains, including the Himalaya, are highly vulnerable ecosystems, especially given climate and land use change. We compiled the literature on Himalayan biodiversity in order to assess spatial and taxonomic trends of research during past 200 years. We identified 35,316 research outputs, including 28,120 journal articles, 3,725 doctoral theses and 3,471 books. Nepal contributes the largest volume of published literature, followed by west Himalayan Indian states, with relatively few studies on the most biodiverse region, lying to the east of Nepal. Publications on Himalayan biodiversity research have increased annually, especially after 1970, with an acceleration since 2000. Among the major taxonomic groups, the largest number of publications is on seed plants (Angiosperms), followed by invertebrates (especially arthropods) and vertebrates. Some groups of organisms notably fungi, bacteria, algae, bryophytes, pteridophytes etc. are clearly under-studied. Among various research disciplines, ecology is the most dominant field followed by agriculture, ethnobiology and paleontology. Some newer disciplines, including molecular biology and climate change, have contributed to the growth in the number of papers appearing during last two decades. Despite an encouraging and rapid increase in research papers during this century, they are largely in low impact factor journals, likely to subject to poor peer review and many doctoral theses remain unpublished. The Government of India’s development initiative emphasizes the importance of research in the Himalaya, which can be enhanced by improved quality of peer review and local journals registering in global indexing services.